OPTIMIZING VILLAGE FUND ALLOCATION TO STRENGTHEN HUMAN RESOURCE CAPACITY IN BUKIT MAKMUR VILLAGE - Mendan, Anugerah; Pratama, M. Aviv Adhitya Putra; Rafdi, Hashfi; Jefri, Jefri; Budiman, Budiman (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2025)
This study aims to analyze the utilization of Village Fund Allocation (ADD) in strengthening human resource capacity in Bukit Makmur Village, Kaliorang Subdistrict, East Kutai Regency. The research approach used is qualitative with a descriptive method. Data were collected through in-depth interviews, direct observation, and documentation studies. Research informants included village officials, community organizations, and beneficiaries selected purposively. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, with triangulation of sources and techniques to ensure data validity. The results of the study show that the use of ADD in Bukit Makmur Village is not only focused on physical development but also directed at human resource development through various community empowerment programs. These programs include job skills training such as sewing, cooking, entrepreneurship, and agricultural product processing, capacity building for village officials through technical guidance, and strengthening social institutions such as the PKK and Karang Taruna. The implementation of these programs has had an impact on improving community competence, economic independence, and social participation. In terms of effectiveness and efficiency, ADD management is considered to be on target and accountable, with a budget realization rate of 99.95% and active community involvement in every stage of the activities.